Адаптация поляризационного базиса антенн базовой станции с ортогональной поляризацией для обеспечения электромагнитной совместимости - Мартынчук, А. А.; Колесников, А. Н. (ХНУРЕ, 2018)
The problem of controlling the polarization basis of antenna systems for radiation in the interest of increasing noise immunity from active noise interference is considered.